Transformation of Paramedics Healthcare Practices into Policy and Public Health Advocacy in the era of Sustainable Development Goals in the Perspective of Nepal - Parajuli, Surya B.; KC, Heera; Mishra, Anjali; Shrestha, Menuka (Journal of College of Medical Sciences-Nepal, 2018)
NA